Evaluation of Hypo-irritancy and Hypo-allergenicity in Cosmetic Products for Scalp - SUGAI, Tetsuro (Skin research, 1996)
An attempt to evaluate the skin safety of three cosmetic products for scalp, that is, scalp lotion S, scalp lotion W and scalp essence, and their eight herb ingredients was made in 30 healthy adult female volunteers. Scarifications 20 minutes' patch test for contact urticaria reactions, scarifications 48 hours' prophetic patch test and photopatch test for irritant reactions as well as photourticarial and phototoxic reactions, and diagnostic patch test 2 weeks later for contact sensitivity were performed. Skin irritation index of the three cosmetic products for scalp was 10.0, 6.7 and 5.0 with scarifications prophetic patch test, while it was 1.7, 0.0 and 1.7 with simple prophetic patch test, respectively. Thus, they are judged as permissible to eczematous scalp and as safe to healthy scal. In scarifications 20 minutes' patch testing, however, contact urticaria was seen in a subject out of the 30 (3.3%), though contact urticaria index was 6.7, 8.3 and 8.3. Therefore, it will be necessary to warn the possibility to induce contact urticaria.